The value of PFS36 as a primary endpoint for radiotherapy trials in patients with LACC: individual patient data from the Chinese NCC and validation from 26 RCTs - Xi Yang; Yuanyuan Zhang; Shuangzheng Jia; Yong Yang; Jie Zhu; Wei Li; Lingying Wu; Jusheng An; Manni Huang (Journal of the National Cancer Center)
Objective: A conventional endpoint for locally advanced cervical cancer (LACC) clinical trials is overall survival (OS) with five years of follow-up. The primary hypothesis was that progression-free survival (PFS) with three years of follow-up (PFS36) would be an appropriate primary surrogate endpoint. Materials and methods: The primary hypothesis, which was developed from our data, was further investigated using phase III randomized controlled trials and then externally validated using retrospective studies up to 2023. Correlation analysis at the treatment-arm level was performed between 2-, 3-, 4-, and 5-year PFS rates and 5-year OS. Results: A total of 613 patients with histologically confirmed cervical cancer who underwent radiotherapy or chemoradiation at our institute between January 2010 and December 2013 were eligible. The recurrence rates for years 1 through 5 were 12.9%, 7.3%, 3%, 2.3%, and 1.8%, respectively. Patients who did not achieve PFS36 had a 5-year OS rate of 30.3%. However, patients who achieved PFS36 had a 5-year OS rate of 98.2%. Further data were extracted from 26 randomized phase III trials on LACC. The trials included 55 arms, with a pooled sample size of 7,281 patients. Trial-level surrogacy results revealed that PFS36 (r2, 0.732) was associated with 5-year OS. The correlation between PFS36 and OS was externally validated using independent retrospective data. Conclusion: A significant positive correlation was found between PFS36 and OS at 5 years of follow-up both within patients and across trials. These results suggest that PFS36 is an appropriate endpoint for LACC clinical trials of radiotherapy-based regimens.